Substituting community children's nursing services for inpatient care: a case study of costs and effects. Issue Volume 31:Issue e1(2014) (28th June 2013) - Callery, Peter; Kyle, Richard G; Weatherly, Helen; Banks, Michele; Ewing, Carol; Powell, Peter; Kirk, Susan
Abstract : Objective: To compare children's pathways to and through Community Children's Nursing Team (CCNT) care, and NHS costs, before and after relocation of inpatient services and extension of a paediatric Emergency Department and Observation and Assessment Unit (ED/OAU). Design: Case study. Routinely collected data on activity and staffing were provided by the CCNT. Parents completed questionnaires about their child's use of healthcare services and satisfaction with care preservice reconfiguration (n=221) or postreconfiguration (n=210). The cost of service use was compared prereconfiguration and postreconfiguration. Patients: Children referred to CCNT care. Main outcome measures: Healthcare service use and associated costs, satisfaction with CCNT care. Results: The mean number of services used before referral to the CCNT reduced from 2.8 to 1.6, and the proportion using only one service increased from 26% (n=58) to 61% (n=128). Inpatient admission during CCNT care reduced from 6% (n=13) to 2% (n=4), and ED attendance from 37% (n=79) to 16% (n=31). There was a considerable fall (25%) in the cost of CCNT care, and a sharp fall (55%) in the average overall NHS cost of care. CCNT care was rated 'excellent' or 'very good' by 85% of respondents both prereconfiguration and postreconfiguration. Conclusions: A CCNT provided an alternative to hospitalisation when acute general paediatric services were reconfigured to substitute for a relocated hospital. Children's pathways to CCNT care were shortened. The average cost of CCNT care and overall NHS cost were lower following reconfiguration. Satisfaction remained high throughout.